Stress granules in neurodegeneration – lessons learnt from TAR DNA binding protein of 43 kDa and fused in sarcoma. (9th May 2013) - Bentmann, Eva; Haass, Christian; Dormann, Dorothee
Abstract : Stress granules (SGs) are cytoplasmic foci that rapidly form when cells are exposed to stress. They transiently store mRNAs encoding house‐keeping proteins and allow the selective translation of stress‐response proteins (e.g. heat shock proteins). Besides mRNA, SGs contain RNA‐binding proteins, such as T cell internal antigen‐1 and poly(A)‐binding protein 1, which can serve as characteristic SG marker proteins. Recently, some of these SG marker proteins were found to label pathological TAR DNA binding protein of 43 kDa (TDP‐43)‐ or fused in sarcoma (FUS)‐positive cytoplasmic inclusions in patients with amyotrophic lateral sclerosis and frontotemporal lobar degeneration. In addition, protein aggregates in other neurodegenerative diseases (e.g. tau inclusions in Alzheimer's disease) show a co‐localization with T cell internal antigen‐1 as well. Moreover, several RNA‐binding proteins that are commonly found in SGs have been genetically linked to neurodegeneration. This suggests that SGs might play an important role in the pathogenesis of these proteinopathies, either by acting as a seed for pathological inclusions, by mediating translational repression or by trapping essential RNA‐binding proteins, or by a combination of these mechanisms. This minireview gives an overview of the general biology of SGs and highlights the recently identified connection of SGs with TDP‐43, FUS and other proteins involved in neurodegenerative diseases. We propose that pathological inclusions containing RNA‐binding proteins, such as TDP‐43 and FUS, might arise from SGs and discuss how SGs might contribute to neurodegeneration via toxic gain or loss‐of‐function mechanisms. Abstract : Stress granules (SGs) are cytoplasmic particles transiently formed in stressed cells. Recently, SG marker proteins were identified to label characteristic TDP‐43‐ or FUS‐positive inclusions found in neurodegenerative diseases such as amyotrophic lateral sclerosis and frontotemporal lobar degeneration. This review provides an overview about SG biology in general and discusses the possible role of SGs in the pathogenesis of neurodegenerative diseases.